Pengembangan Buku Geografi Critical Thinking Materi Indonesia Poros Maritim Dunia untuk SMA/MA - Masitoh, Hastya Rizkananda; Budijanto, Budijanto; Susilo, Singgih (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: This research design used reseach and development design, in the form of geography textbook based on critical thinking in subject of Indonesia's Strategic Position as the World Maritime Axis for SMA/MA. The aim of this research is to observe the feasibility/validity and effectiveness of the developed textbook product. The development used the ADDIE development model. ADDIE development has 5 stages, they are: Analyze, Design, Development, Implement, Evaluation, but this research is only in Implement stage, whileÂ  product testing stage. Data collection methods and data analysis techniques used validation instruments and closed questionnaire sheets with descriptive presentational data analysis techniques. The results of the research and development are obtained total score of the material validator 93% media 95% language 90%, while the average pre-test score of students in the medium category is 44.4%, the low category is 55.5% and the average post-test score of students in the high category is 42% and medium category 30%, and the score regarding the teacher's response to use geography textbooks based on critical thinking is 93%, and the studentâ€™s response score is 92%.Abstrak: Penelitian ini ialah penelitian pengembangan berupa buku teks geografi berbasis critical thinking pada materi Posisi Strategis Indonesia Sebagai Poros Maritim Dunia untuk SMA/MA. Tujuannya untuk melihat kelayakan/kevalidan serta keefektifan produk buku teks yang di kembangkan. Pengembangan menggunakan model pengembangan ADDIE, yang mana pengembangan ADDIE terdapat lima tahapan, yaitu Analyze, Design, Development, Implement, Evaluation, tetapi penelitian ini hanya ditahap Implement, pada tahap uji coba produk. Metode pengumpulan data serta teknik analisis datanya adalah menggunakan instrument validasi dan lembar angket tertutup dengan teknik analisis data deskriptif presentatif. Hasil penelitian dan pengembangan di peroleh hasil skor total oleh validator materi 93 % media 95% bahasa 90%, adapun skor pre test rata-rata siswa berada kategori sedang 44,4%, kategori rendah 55,5% dan skor postest rerata peserta didik kategori tinggi 42%dan kategori sedang 30%, serta skor mengenai respon guru terhadap penggunaan produk buku teks geografi berbasis critical thinking adalah 93%, dan skor respon siswa adalah 92%.